CHARACTERISTICS OF LOCAL INFLAMMATION IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE: DEPENDENCE ON SEVERITY STAGE - L. Yu. Dolinina (SPb RAACI, 2014)
A group of 112 patients with chronic obstructive pulmonary disease of severity were included into the study. Differential cell counts, IL-8, TNFα, and IL-10 concentrations were assayed in sputum and bronchial lavage. The results were compared in groups with different severity of the disease. High levels of macrophages in sputum and bronchial lavage were revealed in COPD of grade 1 and 2. More severe COPD was characterized by mean higher levels of neutrophils in sputum and bronchial lavage. Increased levels of IL-8 and TNFα cytokines have been found in bronchial secretions, independently on COPD severity. Interestingly, maximal levels of these cytokines were associated with mild /moderate stage of the disorder. We have confirmed distinct effects of inhaled corticosteroids upon cytokine levels in sputum and bronchial lavage samples. Sputum proved to be a useful biological material for studies of local inflammatory events in COPD.